OPTIMALISASI E-COMMERCE UNTUK PENINGKATAN DAYA SAING PRODUK UMKM DESA MEKAR SARI NES: E-Commerce, Digital Marketing, Mekar Sari Ness Village, UMKM, Website - Adriana, Windy; Puspitorini, Sukma; Bintang Mahendra, Rizky (JURNAL AKADEMIKA, 2025)
The UMKM product from Mekar Sari Nes Village Batang Hari Regency, sells products produced by UMKM product providers. Sales service is crucial as competition among businesses intensifies. Therefore, the development of an e-commerce sales system to facilitate customer service continues. This research aims to build a web-based e-commerce platform for UMKM products from Mekar Sari Nes Village to overcome traditional marketing constraints such as limited reach, minimal digital promotion, and reliance on direct sales. The research method used is information system development, encompassing needs analysis, design, implementation, testing, and evaluation. The processes involved include product data management, order processing, payments, and notifications. The outputs include sales reports, a monitoring dashboard, and transaction history. The results of the research produce an E-commerce website that has tested the functionality of its core features, such as user registration, product management, checkout process, and payments. This platform is ready to be implemented to support market expansion, increase digital promotion, and reduce dependence on direct sales for UMKM  in Mekar Sari Nes Village.